Mindfulness and Voluntary Work Behavior: Further Support for an Affect Mediation Model - Robinson, Michael D.; Krishnakumar, Sukumarakurup (Frontiers in Psychology, 2022)
Mindfulness, defined in terms of greater attention and awareness concerning present experience, seems to have a number of psychological benefits, but very little of this research has focused on possible benefits within the workplace. Even so, mindfulness appears to buffer against stress and negative affect, which often predispose employees to deviant behaviors. Conversely, mindful employees may be more engaged with their jobs, which could support organizational citizenship. Two studies (total N = 418) pursued these ideas. In Study 1, part-time employees who were higher in dispositional mindfulness were less prone to job negative affect, which in turn predicted lower levels of workplace deviance. In Study 2, more mindful full-time employees were more engaged, and less stressed, and these variables mediated a portion of the relationship between mindfulness and organizational citizenship. Collectively, the two studies link mindfulness to both traditional forms of voluntary work behavior while highlighting mediational pathways.